Knowledge, attitudes, and practices toward colorectal cancer lifestyle risk factors among adults in Saudi Arabia - Alkhaldy, Areej Ali (Frontiers in Nutrition, 2025)
BackgroundDespite an apparent increase in early-onset colorectal cancer (CRC) in Saudi Arabia, with the majority of patients being diagnosed at an advanced disease stage, no previous assessment of the knowledge, attitudes, and practices (KAP) toward its dietary and lifestyle-related risk factors has been reported. The aim of this study was to investigate the KAP levels with respect to these risk factors for CRC and examine possible associations between the studied variables among the Saudi population.MethodsThis cross-sectional study involved 1,040 participants aged 18 years or older. Data were collected by convenience sampling via a self-administered online questionnaire in Saudi Arabia between June and December 2023.ResultsA majority of participants (77.8%) displayed low knowledge about the dietary and lifestyle-related risk factors for CRC, while only 22.2% possessed high knowledge. Similarly, 78.6% of participants exhibited negative attitudes toward these risk factors, with just 21.4% having positive attitudes. Furthermore, 75.0% of participants reported engaging in poor practices, leaving only 25.0% demonstrating good practices related to CRC risk factors.ConclusionsThe findings of this study indicate insufficient KAP levels toward dietary and lifestyle-related risk factors for CRC in Saudi Arabia, highlighting the urgent need for nationwide initiatives and programs to promote improved knowledge, attitudes, and practices and reduce the effect of the risk factors contributing to CRC.